Prevalence of iodine intake inadequacy in elderly Brazilian women. A cross-sectional study - Destefani, S. A.; Corrente, J. E. [UNESP]; Paiva, S. A. R. [UNESP]; Mazeto, G. M. F. S. [UNESP] (Springer, 2015)
Inadequate iodine intake is still a problem in various regions of the world, and limited data exist regarding the ingestion of iodine in elderly people. We investigated the prevalence of iodine intake inadequacy in a group of elderly women living in a region of Brazil considered to be iodine-sufficient.Cross-sectional study conducted in the public healthcare system of Bauru, São Paulo, Brazil.We evaluated 135 elderly women (average age of 68.2 years) who participated in a program of assistance to the elderly with respect to iodine intake through two 24-hour recalls using a nutritional computer program. The women were also evaluated with respect to serum levels of free thyroxin (FT4) and thyrotropin (TSH) and were classified as euthyroid, hypothyroid or hyperthyroid.The average iodine intake of the group was 100.7 +/- 39.2 mu g. Twenty-nine patients (21.5%) presented thyroid dysfunction: 27 (20%) had hypothyroidism, and two (1.5%) had hyperthyroidism. The average iodine intake of the patients with hypothyroidism and euthyroidism was 92.7 mu g and 101.7 mu g, respectively. The prevalence of iodine intake inadequacy, considering the co-variables of age, race, income, body mass index, TSH, FT4 and arterial hypertension, was 51%, 48% and 66% in the general, euthyroid and hypothyroid patients, respectively.We concluded that high prevalence of iodine intake inadequacy was present in this group of elderly women living in a region of Brazil considered to be iodine-sufficient.
Keywords: Elderly nutrition; Hyperthyroidism; Hypothyroidism; Iodine; Nutrients